Demographic details, clinical features, and nutritional characteristics of young adults with Type 1 diabetes mellitus - A South Indian tertiary center experience - Mini Joseph (Indian Journal of Endocrinology and Metabolism, 2016)
Context: Type 1 diabetes mellitus (T1DM) accounts for 5–10% of all diagnosed diabetes and the highest incidence is found in India. Aims: The main objectives were to study the demographic, clinical, and nutritional characteristics of young adults with T1DM and its effect glycosylated hemoglobin levels. Subjects and Methods: This cross-sectional study was conducted among young adults with T1DM (18–45 years of age) in a tertiary hospital in South India. Data were obtained from updated medical records. The dietary data were assessed from food diaries and 24 h recall method. Anthropometry was determined. Results: The analysis revealed that socio-economic variables did not affect the glycosylated hemoglobin levels. The mean glycosylated hemoglobin value was 8.81 ± 2.38%. Nearly, half the patients were malnourished. The overall dietary intake was inadequate. The multivariate regression model, adjusted for confounding factors such as gender, age, and body mass index, revealed that only duration of diabetes and protein intake were significant predictors of glycosylated hemoglobin status (P < 0.005). Conclusion: Integrated care provided at subsidized cost has been pivotal in effective diabetes management. However, there is an urgent need to educate our patients on nutrition therapy. T1DM patients need specialized advice to ensure appropriately balanced nutrition that has a significant impact on their long-term glycemic control.